Pengaruh Kepuasan Kerja, Sikap Kerja dan Loyalitas Kerja Terhadap Kinerja Karyawan Pada PT. Buana Sawit Indah Kabupaten Batu Bara - Lenny Williani; Abdul Rahman (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to determine the partial effect of job satisfaction, work attitude and work loyalty on employee performance at PT. Buana Sawit Indah, Batu Bara Regency. This type of research is quantitative, data analysis uses multiple linear regression, and involves a sample of 58 respondents determined by the slovin method from a total of 139 employees. The results of the t-test prove that H0 is rejected while H1 is accepted, namely partially job satisfaction influences employee performance with a t-value (7.832) > t-table (2.004), work attitude influences employee performance with a t-value (2.533) > t-table (2.004) and work loyalty influences employee performance with a t-value (3.042) > t-table (2.004). The F-test results prove that H0 is rejected while H2 is accepted, namely that job satisfaction, work attitude, and work loyalty influence employee performance, with the calculated F value > F table (34.662 > 2.78). The results of the coefficient of determination analysis (R2 test) show that the adjusted R-square value is 0.639, meaning that the variables of job satisfaction, work attitude, and work loyalty contribute 63.9% to employee performance, while the remaining 36.1% is influenced or explained by other variables not included in this study.